2014
DOI: 10.1111/bjd.13220
|View full text |Cite
|
Sign up to set email alerts
|

Clinical epidemiology of hand eczema in patients accessing dermatological reference centres: results from Italy

Abstract: Chronic hand eczema is frequent among patients with hand eczema accessing dermatology centres. Many patients were severe and refractory to standard therapy. The appropriate identification of hand eczema is the first step in implementing effective and efficient treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 36 publications
0
7
0
4
Order By: Relevance
“…One more important finding related to atopic dermatitis is that subjects with hand eczema who have a personal history of atopic dermatitis tend to be more severely affected in their daily life. In Italian hand eczema patients (n = 766), clinically severe and refractory hand eczema has been reported to be significantly more common among patients with atopic dermatitis than among those with non‐severe hand eczema (OR 2.16, 95%CI: 1.12–4.17) . A recent study in Swedish adolescents showed that moderate/severe atopic dermatitis was significantly associated with hand eczema (OR 3.0, 95%CI: 1.5–6.0), but the OR for mild atopic dermatitis was lower (OR 1.3) and not significant .…”
Section: Discussionmentioning
confidence: 99%
“…One more important finding related to atopic dermatitis is that subjects with hand eczema who have a personal history of atopic dermatitis tend to be more severely affected in their daily life. In Italian hand eczema patients (n = 766), clinically severe and refractory hand eczema has been reported to be significantly more common among patients with atopic dermatitis than among those with non‐severe hand eczema (OR 2.16, 95%CI: 1.12–4.17) . A recent study in Swedish adolescents showed that moderate/severe atopic dermatitis was significantly associated with hand eczema (OR 3.0, 95%CI: 1.5–6.0), but the OR for mild atopic dermatitis was lower (OR 1.3) and not significant .…”
Section: Discussionmentioning
confidence: 99%
“…The hands were both initially and currently the most prevalent sites in the cobalt group. Hand dermatitis is also one of the most frequent dermatological disorders . Many factors may predispose to hand eczema, including genetic predisposition, atopic dermatitis, other contact allergies, and wet work.…”
Section: Discussionmentioning
confidence: 99%
“…En cuanto a la gravedad de la enfermedad, un estudio de la población italiana con EM reveló que el EM era crónico en el 83,5% de los pacientes; el 21,3% tenían eccema grave, y el 62,0% eran refractarios al tratamiento estándar 12 . Del registro CARPE de pacientes alemanes con ECM, el ECM fue muy grave en el 23,4%, grave en el 47,0%, moderado en el 20,1% y leve o muy leve en el 9,6% de los pacientes 13 .…”
Section: Epidemiologíaunclassified
“…Como el EM puede tener implicaciones a nivel profesional y puede ser considerado como una enfermedad profesional, su impacto social y económico es significativo. Los trabajadores con mayor riesgo eran los que realizaban el procesamiento de alimentos y trabajos que implicaban el constante contacto con agua, como los profesionales de la salud o la peluquería, entre otros 12 . Los trabajadores de la salud han sido detectados como un grupo de alto riesgo en estudios realizados en Canadá 30 , Corea 18 , Países Bajos 31 , Dinamarca 19,28,32 , Noruega 8 y Alemania 15 , con prevalencias en este grupo que oscilan entre el 21,0 y el 47,0%.…”
Section: Factores De Riesgounclassified